Allelic variation in an expansin, MdEXP-A1, contributes to flesh firmness at harvest in apples - Qiufang Su; Yifeng Feng; Xianglu Li; Zidun Wang; Yuanwen Zhong; Zhengyang Zhao; Huijuan Yang (Molecular Horticulture)
Abstract Flesh firmness is a core quality trait in apple breeding because of its correlation with ripening and storage. Quantitative trait loci (QTLs) were analyzed through bulked segregant analysis sequence (BSA-seq) and comparative transcriptome analysis (RNA-seq) to explore the genetic basis of firmness formation. In this study, phenotypic data were collected at harvest from 251 F1 hybrids derived from ‘Ruiyang’ and ‘Scilate’, the phenotype values of flesh firmness at harvest were extensively segregated for two consecutive years. A total of 11 candidate intervals were identified on chromosomes 03, 05, 06, 07, 13, and 16 via BSA-seq analysis. We characterized a major QTL on chromosome 16 and selected a candidate gene encoding expansin MdEXP-A1 by combining RNA-seq analysis. Furthermore, the genotype of Del-1166 (homozygous deletion) in the MdEXP-A1 promoter was closely associated with the super-hard phenotype of F1 hybrids, which could be used as a functional marker for marker-assisted selection (MAS) in apple. Functional identification revealed that MdEXP-A1 positively expedited fruit softening in both apple fruits and tomatoes that overexpressed MdEXP-A1. Moreover, the promoter sequence of TE-1166 was experimentally validated containing two binding motifs of MdNAC1, and the absence of the MdEXP-A1 promoter fragment reduced its transcription activity. MdNAC1 also promotes the expression of MdEXP-A1, indicating its potential modulatory role in quality breeding. These findings provide novel insight into the genetic control of flesh firmness by MdEXP-A1.